A project‐based learning approach to promote innovation and academic entrepreneurship in a master's degree in food engineering. Issue 4 (21st September 2021) - Oliveira, Leandro; Cardoso, Eduardo L.
Abstract: Entrepreneurship brings several benefits, such as fostering innovation and productivity, competitiveness, and socioeconomic development. The search for professionals with different skills to overcome the current and foreseen challenges is relevant in the agri‐food sector. Problem‐based learning (PBL) is described as an instructional approach, which promotes interdisciplinarity and critical thinking, with the potential to meet current challenges. This article describes how PBL, aligned with an innovation program and contest, has been integrated into a master's degree in food engineering to promote academic entrepreneurship. The alignment of the PBL with the program and contest allowed the development of innovative products with a view to solving problems faced by the agri‐food sector. The PBL strategy allowed students to mobilize knowledge from several curricular units of food studies for the development of different deliverables to participate in the innovation program and contest. This participation allowed students, supported by business mentors, to demonstrate their products to stakeholders. This way, it was possible to promote innovation in the agri‐food sector, stimulating the entrepreneurial spirit among higher education students, and understand its potential for replication and mobilization of skills acquired in different food study courses.